TREATMENT EFFECTIVENESS OF ANTIHELMINTHIC PREPARATIONS FOR GOAT DIGESTIVE TRACT STRONGYLATOSES - Melnychuk, V. V.; Chubarov І. V. (Scientific Progress & Innovations, 2020)
Digestive tract strongylatoses are the most widely spread diseases in the nosological structure of parasit- ic diseases of wild and domestic ruminants, including goats (Capra hircus Linnaeus, 1758). The representa- tives of Strongylata sub-species (Railliet et Henri, 1913) in case of parasitizing in the organism can cause irreversible processes negatively affecting both the productivity and animal health on the whole. That is why the question of studying the effectiveness of anti-helminthic preparations available on the pharmaceutical market of our country is important. Despite a considerable number of anti-helminthic means, it is often diffi- cult for practicing veterinary doctors to choose highly effective and not expensive preparation. In this con- nection the aim of our study was to estimate anti-helminthic effectiveness of the preparations of benzimidazol chemical group (“Albendazol-250”, “10 % Albendazol suspension”, and “10 % Albendazol for injections”) for the treatment of goat digestive tract strongylatoses taking into account the way of their administration. For the experiments studying the indices of anti-helminthic effectiveness, 4 groups of goats (3 experimental and 1 control one) were formed at the average intensity of strongylatosis invasion from 59.33±9.38 to 70.67±11.25 eggs/g of feces. The preparations used in the experiments were given to the diseased animals in accordance with recommendation in supplementary sheet. It was established that the studied preparations had anti-helminthic effect as to causative agents of goat digestive tract strongylatoses (ЕЕ – 50–100 %, ІЕ – 87.53–100 %). It was proven that the preparations’ effectiveness depended on the way of their administra- tion. “10 % Albendazol for injections” turned out to be the most effective (EE and IE 100 %); it was injected to animals intra-muscularly only one time at a dose of 0.5 ml / 10 kg of body weight. “10 % Albendazol sus- pension” was less effective(ЕЕ – 83.33 %, ІЕ – 93.99 %); it was individually watered to the animals. Admin- istering “Albendazol-250” in tablets to the diseased goats had the lowest indices of effectiveness (ЕЕ – 50.00 %, ІЕ – 87.53 %). Thus, the data obtained by us have important theoretical and practical value as they enable practicing veterinary doctors to choose anti-helminthic preparation for the treatment goat digestive tract strongyladoses invasion taking into account the effectiveness of preparations.